Analysis of English Language Hegemony in Digital Marketing Content in Indonesia - Prabowo, Bayu Ade; Rahmad Satato, Yuniarto; Rafli Nurmeidy, Agi; Bernike Kurnia Eka Sugiarto, Euodia (Universitas Dian Nuswantoro, 2024)
This study examined the prevalence of English in digital marketing content among Indonesian startups, exploring the balance between global linguistic trends and local language use in an emerging digital economy. The research analyzed digital marketing materials from 10 prominent Indonesian startups across various sectors using qualitative content analysis. The findings reveal a strategic bilingual approach, with 42.3% English, 53.7% Indonesian, and 4.0% mixed language use overall. Significant variations were observed across digital platforms, industry sectors, and content types. Websites and app descriptions showed higher English usage, while social media favored Indonesians. Technology and fintech startups used more English (56.8%), contrasting with education and healthcare startups' preference for Indonesian (70.4%). Theoretically, this study contributes to understanding of strategic bilingualism and linguistic adaptation in digital marketing by demonstrating how language choices reflect both global aspirations and local market demands. Empirically, the findings reveal that Indonesian startups employ a systematic approach to language selection across different platforms and sectors, with technology companies favoring English (56.8%) while education and healthcare sectors predominantly use Indonesian (70.4%), indicating a careful balance between international reach and local engagement in their digital marketing strategies.